Radiation Nephritis: III. Chemical, Functional and Morphologic Correlates of the Glomerular Basement Membrane - Gang, N. F. (1973)
In the rat, radiation injury to a kidney results in severe glomerular lesions, with only a moderate increase in proteinuria. The proteinuria, however, was found to be nonselective. There was no relationship between the degree and selectivity of the proteinuria. No change in the gross chemical composition of the glomerular basement membrane obtained from the irradiated kidney was observed when compared with the GBM of a) untreated control kidneys, b) kidneys obtained from sham operated rats, c) unilaterally nephrectomized and d) control kidneys of irradiated animals. In conclusion, no correlation could be established between the morphologic alterations of the glomerulus and the chemical or permeability characteristics of the membrane.